2015
DOI: 10.1159/000439434
|View full text |Cite
|
Sign up to set email alerts
|

Grade Increases in Gastroenteropancreatic Neuroendocrine Tumor Metastases Compared to the Primary Tumor

Abstract: Background/Aim: The neuroendocrine tumor (NET) proliferation-based grading system (ENETS/WHO) for gastroenteropancreatic (GEP) tumors has proved reliable for prognostic stratification. To date, concerns exist regarding Ki-67 heterogeneity within the tumor and little is known on whether grade varies between primary and secondary sites. As tumor heterogeneity may have a significant impact on clinical management, our aim was to retrospectively evaluate Ki-67 on a series of GEP NETs in order to establish whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 24 publications
(35 reference statements)
4
67
0
2
Order By: Relevance
“…This examination and previous studies [10,12,15,24] showed that pancreatic NEN (in particular NET) may show heterogeneous distribution of Ki67 LI. Unfortunately, adherence to WHO 2010 scoring criteria did not allow providing precise reports of tumour grade in a subset of pancreatic NET, at least from a single patient perspective.…”
Section: Toward Optimal Methods Of Ki67 LI Assessmentsupporting
confidence: 80%
See 3 more Smart Citations
“…This examination and previous studies [10,12,15,24] showed that pancreatic NEN (in particular NET) may show heterogeneous distribution of Ki67 LI. Unfortunately, adherence to WHO 2010 scoring criteria did not allow providing precise reports of tumour grade in a subset of pancreatic NET, at least from a single patient perspective.…”
Section: Toward Optimal Methods Of Ki67 LI Assessmentsupporting
confidence: 80%
“…Grillo et al reported that 37% (22/60) of gastro-entero-pancreatic NEN showed different Ki67 LI between tissue blocks of primary tumour (2-5 paraffin block were examined per case). However, only in 5% (3/60) of cases this resulted in change of grade from G1 to G2 [15]. This value could be underestimated, since higher grade component may form a minor portion of the tumour [9].…”
Section: Ki67 LI Heterogeneity Beyond Single Hs or Csmentioning
confidence: 95%
See 2 more Smart Citations
“…В связи с внутриопухолевой гетерогенностью данного параметра и возможным несовпадением мито-тического индекса и индекса Ki-67 важно оценивать заболевание с учетом наиболее высокого показателя пролиферативной активности опухолевых клеток. По-следние исследования показали, что индекс Ki-67 яв-ляется непостоянным параметром, который может зна-чительно меняться в процессе опухолевой прогрессии, поэтому его определение рекомендуется проводить не только в первичной опухоли, но и в биопсиях мета-стазов [46][47][48].…”
Section: дифференци-ровка степень злокачест-венности (G) категорияunclassified